Peran Pendidikan Islam Dalam Membentuk Karakter Siswa Sekolah Dasar - Al-Adawiyah, Rabbiah; Prastika, Silfa Ayu; Arefanda, Vera; Wicaksono, Hanif Nur (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the role of Islamic Religious Education (IRE) in shaping the character of elementary school students with an emphasis on key values such as honesty, discipline, responsibility, empathy, and tolerance. This study uses a systematic literature review method of empirical research results and contemporary Islamic education theories. The findings indicate that PAI not only serves as a medium for transferring religious knowledge but also as the primary agent in internalizing moral and spiritual values into the daily lives of students. The study's findings show that an effective PAI curriculum must integrate theoretical learning and practical application through innovative learning models such as blended learning, the use of digital media, and collective worship routines—for example, congregational prayer, Quran recitation, and participation in social projects. The success of character development is also strengthened by the synergy between schools, teachers, families, and communities, who collectively serve as role models, educators, and reinforcers of the process of habituating Islamic values. Literature analysis also reveals that the implementation of innovative learning models, such as blended learning and the use of digital media, enhances the effectiveness of Islamic Education (PAI) in instilling these character values, proven to promote the consistent practice of Islamic values by students, both within and outside the school environment.